AB1018 Challenge of Treatment After Adverse Effects Caused by Biological Therapy. (9th June 2015) - Srsen, S.; Marusic, E.; Metlicic, V.; Stricevic, L.; Frkovic, M.; Jelusic, M.
Abstract : Background: Biological agents are widely used in treatment of autoimmune rheumatic disorders. Use of biological agents, including anti – TNF receptor antibodies, is recognized as a risk factor for a serious adverse effects, primarily infections, including tuberculosis, but also other adverse effects including neurological. (1 – 3) There are no guidelines how to treat patients afterwards. Objectives: To describe two cases of serious adverse effects during anti – TNF treatment and emphasise the need of developing guidelines for further treatment of such patients. Results: First patient is a 7 year old girl treated for juvenile idiopatic arthritis since the age of two, and starting treatment with anti – TNF inhibitor at the age of 4 due to developing uveitis. Twenty months after introduction of adalimumab she developed disseminated tuberculosis that was successfully treated with antituberculotic drugs. Second patient is 14 year old boy who was treated for juvenile spondyloarthritis since the age of four, and who developed inflammatory process of central nervous system 17 months after initiation of anti – TNF inhibitor (adalimumab), manifesting with severe headache, vertigo, muscle weakness, loss of sense of his left arm, strong tremor and spontaneous myoclonism of larger groups of muscles. Pleocytosis in cerebrospinal fluid (CSF) was present, with more IgG oligoclonal bands positive, with no blood – CSF barrier dysfunction, implicating active inflammatory process of CNS. He was treated with corticosteroids and symptoms eventually diminished, with residual neurological sequelae. Conclusions: During treatment with biological agents adverse events may occur, but there are no recommendations of how to treat patients afterwards. We are planning to start treatment with abatacept in case of another flare of disease in a girl with JIA, while in a boy with juvenile spondyloarthritis and inflammatory process of CNS, we do not have intentions of reintroducing biological therapy because boy and his family are not willing of starting biological treatment again. We would like to emphasize a need of creating and developing guidelines for further treatment of such a patients since individual experiences in literature are seldom and scarce, and to the best of our knowledge there are no any recommendations or guidelines for further treatment of such patients. References: Nanau RM, Neuman MG. Safety of anti-tumor necrosis factor therapies in arthritis patients. J Pharm Pharm Sci. 2014;17(3):324-61. Dixon WG, Hyrich KL, Watson KD, et al. Drug-specific risk of tuberculosis in patients with rheumatoid arthritis treated with anti-TNF therapy: results from the British Society for Rheumatology Biologics Register (BSRBR). Ann Rheum Dis. 2010 Mar;69(3):522-8. Deepak P, Stobaugh DJ, Sherid M, et al. Neurological events with tumour necrosis factor alpha inhibitors reported to the Food and Drug Administration Adverse Event Reporting System. Aliment Pharmacol Ther. 2013 Aug;38(4):388-96. Disclosure of Interest: None declared